.8x-1.1(x-3)=.2(x-6)

Simple and best practice solution for .8x-1.1(x-3)=.2(x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .8x-1.1(x-3)=.2(x-6) equation:


Simplifying
0.8x + -1.1(x + -3) = 0.2(x + -6)

Reorder the terms:
0.8x + -1.1(-3 + x) = 0.2(x + -6)
0.8x + (-3 * -1.1 + x * -1.1) = 0.2(x + -6)
0.8x + (3.3 + -1.1x) = 0.2(x + -6)

Reorder the terms:
3.3 + 0.8x + -1.1x = 0.2(x + -6)

Combine like terms: 0.8x + -1.1x = -0.3x
3.3 + -0.3x = 0.2(x + -6)

Reorder the terms:
3.3 + -0.3x = 0.2(-6 + x)
3.3 + -0.3x = (-6 * 0.2 + x * 0.2)
3.3 + -0.3x = (-1.2 + 0.2x)

Solving
3.3 + -0.3x = -1.2 + 0.2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.2x' to each side of the equation.
3.3 + -0.3x + -0.2x = -1.2 + 0.2x + -0.2x

Combine like terms: -0.3x + -0.2x = -0.5x
3.3 + -0.5x = -1.2 + 0.2x + -0.2x

Combine like terms: 0.2x + -0.2x = 0.0
3.3 + -0.5x = -1.2 + 0.0
3.3 + -0.5x = -1.2

Add '-3.3' to each side of the equation.
3.3 + -3.3 + -0.5x = -1.2 + -3.3

Combine like terms: 3.3 + -3.3 = 0.0
0.0 + -0.5x = -1.2 + -3.3
-0.5x = -1.2 + -3.3

Combine like terms: -1.2 + -3.3 = -4.5
-0.5x = -4.5

Divide each side by '-0.5'.
x = 9

Simplifying
x = 9

See similar equations:

| 1/3X=-1 | | 18y-6-6y=10 | | 12t-10=14t+2findt | | 1+4+2=1-4+4 | | -42g-150=25 | | 45c-73=-24 | | 12x+1=4-3+6 | | 6x-6=6-2 | | 10y-13y+14y= | | -3/5(-12.5)+3=y | | 1/2x+3=8 | | 7/(2x5^3)+3/(4x5^2) | | x^2+4x-1085=0 | | 21/4/3/8 | | 4+3y-3=-15 | | D=R(1-DT) | | -3/4+2/7 | | 4x=508 | | x+9-2x=10-22-4x | | v+v-33.6+v-24.8=197.0 | | 7x-48=259 | | v+v-33.6+v+24.8=197.0 | | 1/2a+5=-1/2a | | 110/6=x/4 | | -1/2-6/7 | | -5/9+2/3 | | 63+-1= | | 2n(n+3)-5(n+3)= | | 15-10=80 | | 5(y-1)=3y+5-2(-7y+3) | | 3x-14=4x-18 | | 3y-17=-4 |

Equations solver categories